Facial injuries in sports - Romeo, S. J.; Hawley, C. J.; Romeo, M. W.; Romeo, J. P. (The Physician and Sportsmedicine, 2005)
A team physician's guide to diagnosis and treatment of facial injuries in sports. Team physicians must be prepared to manage facial injuries, including contusions, abrasions, lacerations, nasal fractures, septal hematomas, auricular hematomas, ruptured tympanic membranes, and fractures of the facial bones. With a focused history and a thorough physical exam, the diagnosis can be clearly established. Early treatment of sports-related facial injuries helps avoid complications, and athletes may expect to return to play after predictable time intervals.